Lasers to prevent dental caries: a systematic review - Stefano Pagano; Guido Lombardo; Massimiliano Orso; Iosief Abraha; Benito Capobianco; Stefano Cianetti (BMJ Open)
Objective To assess the effectiveness of lasers (at sub-ablative parameters) in reducing caries incidence compared with traditional prophylactic interventions (TPIs) when used alone or together with other TPIs such as pits and fissures sealant or fluoride gels or varnishes.Design A systematic review. Data sources include Medline (via PubMed), Embase, Web of Science and the Cochrane Library (December 2019).Eligibility criteria Only randomised trials (RCTs) and controlled clinical trials (CCTs) dealing with prophylactic lasers use (vs TPI or untreated teeth) were considered as eligible. We excluded in vitro and ex vivo studies.Data extraction Eligible studies were selected and data extracted independently by two reviewers. Risk of bias was assessed adopting the Cochrane Risk of Bias tool. Data on caries incidence, sealant retention, fluoride uptake, adverse events, treatment duration, patients’ discomfort and cost-effectiveness ratio was extracted.Data analysis Extracted data were presented narratively due to the heterogeneity of included studies.Results Seven RCTs and two CCTs, all with an evident risk of bias, met inclusion criteria, pooling together 269 individuals and 1628 teeth. CO2, neodymium-doped yttrium aluminium garnet, erbium-doped yttrium aluminum garnet (Er:YAG), erbium, chromium: yttrium scandium gallium garnet (Er,Cr:YSGG) and Argon lasers were used. In the permanent dentition, lasers only when used in combination with TPIs were effective in reducing caries when compared with untreated teeth (risk ratio (RR)=0.44 (0.20–0.97); Er:YAG laser) or with TPIs used alone (RR=0.39 (0.22–0.71); CO2 laser). Moreover, Argon laser significantly improved the fluoride uptake into the enamel surfaces (ANalysis Of VAriance (ANOVA) tests: 95%, p<0.0001). Likewise, sealant retention improved when acid etching was performed on previously irradiated enamel fissures by CO2 laser (RR=0.63 (0.38–1.04)) or Er:YAG laser (RR=0.54 (95% CI: 0.34 to 0.87)). In addition, laser resulted safe and well tolerated by patients.Conclusion Despite some positive indications, an inadequate level of evidence was found in the included studies concerning the lasers’ effectiveness in preventing caries. Further studies with a higher methodological quality level are required.